UK guidelines on 18F-fluciclovine PET/CT in prostate cancer imaging. Issue 7 (July 2019) - Afaq, Asim; Gleeson, Fergus; Scarsbrook, Andrew; Bradley, Kevin; Subesinghe, Manil; Macpherson, Ruth; Haroon, Athar; Patel, Neel; Chua, Sue; Wong, Wai-Lup; Vinjamuri, Sobhan; Warbey, Victoria S.; et al.
Abstract : The purpose of these guidelines is to assist specialists in Nuclear Medicine and Radionuclide Radiology in recommending, performing, interpreting and reporting 18 F-fluciclovine PET/computed tomography. It should be recognised that adherence to the guidance in this document will not assure an accurate diagnosis or a successful outcome. These guidelines will assist individual departments in the formulation of their own local protocols. The guidelines apply to studies on adults. All that should be expected is that the practitioner will follow a reasonable course of action based on current knowledge, available resources and the needs of the patient in order to deliver effective and safe medical care.